Complete mitochondrial genome of the hybrid grouper Hyporthodus septemfasciatus (♀) × Epinephelus lanceolatus (♂). Issue 3 (2nd July 2020) - Park, Jong Yeon; Kim, Yong-Hwi; Bang, In-Chul
Abstract: The complete mitochondrial genome of the novel hybrid grouper ( Hyporthodus septemfasciatus ♀ × Epinephelus lanceolatus ♂) includes 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNA genes, and 1 control region (D-loop) for a total length of 16, 559 bp. The overall nucleotide composition encoded on the heavy strand comprises 28.64% A, 28.26% C, 16.26% G, and 26.84% T.